Zakat as an Alternative Policy for Local Government in Alleviating Poverty (Case Study in Ternate City Government) - Abd Rauf Wajo (Jurnal Economic Resource, 2021)
This study aims to analyze zakat as a local government policy for the city of Ternate in alleviating poverty. The research approach used is qualitative. The data and information collection techniques used are qualitative data collection techniques, including observa-tional studies, in-depth interviews, documentation studies, and literature studies. Data analysis in this research will be carried out through several stages, namely, data reduc-tion, data display, understanding interpretation and interpretation, conclusion, and verification. The research results are, zakat as an alternative policy on poverty allevia-tion in Ternate City by the local government of Ternate City, regarding tagline of Ter-nate (e.g., Ternate cares, Ternate is smart, Ternate is taqwa, Ternate is prosperous, and Ternate is healthy). That has been implemented in the city of Ternate, even though every Local Government rarely carries out policies like this because every poverty alleviation policy is generally based on conventional bureaucratic procedures.